2022
DOI: 10.3390/fermentation8030123
|View full text |Cite
|
Sign up to set email alerts
|

Looking inside Mexican Traditional Food as Sources of Synbiotics for Developing Novel Functional Products

Abstract: Currently, emerging alimentary alternatives are growing, leading to the consumption of natural products including bio, fermented, and traditional foods. The studies over functional properties of food matrices and their derived compounds have resulted in the development of new functional alimentary items. However, most of the population still has limited access to, and information about, suitable foods. Analyzing traditional fermented products, we found fermented food matrices containing beneficial bacteria, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 138 publications
0
8
0
Order By: Relevance
“…Traditional Mexican foods have been associated with improvements in the gut microbiota in experimental studies in murine models of metabolic disease [ 75 ] and recently in patients with metabolic syndrome [ 76 ]. Specifically, maize ( Zea mays L.), nopal ( Opuntia ficus ), and beans ( Phaseolus vulgaris L.) have food matrices that may contain beneficial bacteria, prebiotic fibers, and polyphenols that may be beneficial for the gut microbiome [ 77 ]. For example, nixtamalized corn contains prebiotic compounds such as ferulated arabinoxylans, which can promote the growth of Bifidobacterium and increase the production of SCFAs [ 77 ].…”
Section: Potential Benefits For People With Ckd ( Figure 2 ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional Mexican foods have been associated with improvements in the gut microbiota in experimental studies in murine models of metabolic disease [ 75 ] and recently in patients with metabolic syndrome [ 76 ]. Specifically, maize ( Zea mays L.), nopal ( Opuntia ficus ), and beans ( Phaseolus vulgaris L.) have food matrices that may contain beneficial bacteria, prebiotic fibers, and polyphenols that may be beneficial for the gut microbiome [ 77 ]. For example, nixtamalized corn contains prebiotic compounds such as ferulated arabinoxylans, which can promote the growth of Bifidobacterium and increase the production of SCFAs [ 77 ].…”
Section: Potential Benefits For People With Ckd ( Figure 2 ...mentioning
confidence: 99%
“…Specifically, maize ( Zea mays L.), nopal ( Opuntia ficus ), and beans ( Phaseolus vulgaris L.) have food matrices that may contain beneficial bacteria, prebiotic fibers, and polyphenols that may be beneficial for the gut microbiome [ 77 ]. For example, nixtamalized corn contains prebiotic compounds such as ferulated arabinoxylans, which can promote the growth of Bifidobacterium and increase the production of SCFAs [ 77 ]. Corn cobs are sources of xylooligosaccharides with prebiotic properties promoting the production of SCFAs and the growth of L. plantarum S2, which may have antimicrobial effects limiting pathogenic bacteria and maintaining gut homeostasis [ 77 ].…”
Section: Potential Benefits For People With Ckd ( Figure 2 ...mentioning
confidence: 99%
“…Researchers have suggested that traditional food should be viewed as a source of synbiotics for developing novel functional products [73]. The science of fermented foods is complicated and complex to explain how these foods can benefit health.…”
Section: Fermented Foodsmentioning
confidence: 99%
“…Recent research into the extraction and generation of novel bioactive compounds (for example, saponins and antioxidants) indicates more opportunities for the agave value chain industry [ 22 ]. More and more attention has been paid to fructose-rich syrups in recent times, which have become the most demanded sweeteners by the global pharmaceutical and food industries thanks to their technological and functional advantages over sucrose, and their beneficial health effects [ 11 , 25 ] in relation to the bioactive compounds present (fructanes amino and acids) [ 26 ]. All of this confers antibacterial properties and antioxidant capacity.…”
Section: Food Industry Applications and Sustainability Issuesmentioning
confidence: 99%
“…Traditional processing to exploit agave as a source of bioactive compounds and carbohydrate-rich syrups can be performed for direct use or as substrates to yield spirits and hydrolyzed fermented products [ 21 , 26 ].…”
Section: Food Industry Applications and Sustainability Issuesmentioning
confidence: 99%